2016
DOI: 10.1038/srep26090
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen responsive transcriptome in potato (Solanum tuberosum L.) reveals significant gene regulatory motifs

Abstract: Nitrogen (N) is the most important nutrient for the growth of potato (Solanum tuberosum L.). Foliar gene expression in potato plants with and without N supplementation at 180 kg N ha−1 was compared at mid-season. Genes with consistent differences in foliar expression due to N supplementation over three cultivars and two developmental time points were examined. In total, thirty genes were found to be over-expressed and nine genes were found to be under-expressed with supplemented N. Functional relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 65 publications
(109 reference statements)
2
20
0
2
Order By: Relevance
“…Over the years many transcriptomic studies have been conducted to understand plant response to high and low concentration of N. They showed that various biological processes, such as amino and nucleic acid synthesis, protein folding, RNA processing, and hormone biosynthesis are rapidly affected when nitrate is depleted or resupplied . Recently, the role of genes taking part in amino acid metabolism was emphasized by transcriptomic study in potato . However, as yet, few equivalent studies at the proteomic level have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years many transcriptomic studies have been conducted to understand plant response to high and low concentration of N. They showed that various biological processes, such as amino and nucleic acid synthesis, protein folding, RNA processing, and hormone biosynthesis are rapidly affected when nitrate is depleted or resupplied . Recently, the role of genes taking part in amino acid metabolism was emphasized by transcriptomic study in potato . However, as yet, few equivalent studies at the proteomic level have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…ncbi.nlm.nih.gov/geo/) -это база данных, в которой собра ны результаты высокопроизводительного секвенирования транскриптомов (RNAseq) и анализа экспрессии генов с использованием микрочипов, в том числе для S. tuberosum (Rensink et al, 2005;Carvallo et al, 2011;Evers et al, 2012;Zhang et al, 2013;Stare et al, 2015;Gálvez et al, 2016). База данных GEO включает несколько разделов, в том числе DataSets, который содержит описание эксперимен тов по секвенированию транскриптомов.…”
Section: транскриптомные исследования как ключ к пониманию механизмовunclassified
“…В этом разделе суммированы данные 1 583 экспериментов, посвященных анализу транскриптома картофеля. Результаты транс криптомных экспериментов в БД GEO представлены в 30 публикациях, в число которых входят исследования по изменению транскриптома картофеля в ответ на за ражение вирусами Petek et al, 2014;Stare et al, 2015), на воздействие факторами абиотического стресса (Gálvez et al, 2016), различия в уровне экспрессии генов miRNA в зависимости от стадии развития (Lakhotia et al, 2014). Первичные данные секвенирования транс криптомов в экспериментах RNAseq представлены в базе данных NCBI SRA (Sequence Read Archive), основном мировом архиве результатов высокопроизводительного секвенирования нуклеотидных последовательностей.…”
Section: транскриптомные исследования как ключ к пониманию механизмовunclassified
“…Recently, Gálvez et al. (Gálvez, Tai, Lagüe, Zebarth, & Strömvik, 2016) identified 30 over‐expressed genes and 9 under‐expressed genes in potato ( Solanum tuberosum L.) with supplemented NO 3 − . These findings highlight the case to further investigate the potential regulatory mechanisms of gene in flue‐cured tobacco in response to NO 3 − supply.…”
Section: Introductionmentioning
confidence: 99%